Storage Stability of High Fiber Snack Bar - Pratiwi, Ivana Aprilia; Kemsawasd, Varongsiri; Winuprasith, Thunnalin (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Recently, there has been considerable interest in increasing the dietary fiber content in food products because of inadequate dietary fiber consump on when considering the daily recommended intake. To in- crease dietary fiber intake, dietary fiber for fied foods are recommended. This study aimed to develop a high fiber snack bar (HFSB) using a combina on of Jerusalem ar choke powder (JAP) and low-fat desiccated coconut (LFDC) as sources of dietary fiber. Methods: The changes in physicochemical and microbiological proper es, and sensory acceptability were mea- sured during storage at 35 oC and 45 oC for 12 weeks. Therefore, the shelf-life of the products was calculated by Q10 test. Results: The HFSB had a higher L* value (lightness) than control (C) due to the addi on of LFDC. Total dietary fiber of the HFSB was approximately 3.7 mes higher than that of the C formula. The L*, a*, and b* values of both C and HFSB were sta s cally significant different (p<0.05) a er storage. The total color different ( E) values of the HFSB were higher than those of the C formula due to inulin from JAP, which par cipated in the Maillard reac on. During storage, the moisture content (MC) and water ac vity (aw) of the HFSB remained more stable compared to those of the C due to the water-holding capacity of the fiber used. The aw of the C and HFSB during storage were in the range of 0.57to 0.60 and 0.53 to 0.57, respec vely. Those ranges should be stable against microbial growth. Higher storage temperature would increase the TBARS values and decrease the pH (p<0.05) of the C and HFSB due to deteriora on. In terms of shelf-life calcula on, the C and HFSB snack bar could be kept in metalized polyester at 30 oC for 11 weeks. Conclusion: The JAP and LFDC exhibited great poten al for use as fiber ingredients. Although the JAP and LFDC influenced the physicochemical proper es and sensory acceptability, the shelf-life of both C and HFSB was com- parable. Therefore, further studies should be conducted to extend the shelf-life of the formulated snack bar.